Intensive White Snapper Pond Cultivation Technology (Lates calcarifer) in Order to Diversify Pond Business in Majannang Village - Mulyani, Sri; Pallu, Muhammad Saleh; Mardiana, Mardiana; Fikruddin, Muhammad; Yunus, Muhammad Kafrawi; Fatmawati, Fatmawati; Handayani, Hainun Putri; Ningsi, Sitti Warda (International Journal of Public Devotion, 2023)
PT. Bosowa Isuma as a partner in the Kedaireka 2022 Matching Fund Program has not diversified commodities and production results in carrying out cultivation activities. The purpose of this activity is to carry out the cultivation of white snapper (Lates calcarifer) in order to diversify the cultivation business. The method of implementation by training and application of white snapper farming in a 5,000 m2 fish pond owned by PT. Bosowa Isuma. The stages of implementation in the form of training and application of pond cultivation include: 1) Preparation of ponds; 2) Seed stocking; 3) Feeding; 4) Sampling and Grading; 5) Water quality measurement; 6) Pest and disease control; 7) Harvesting. The results obtained were in the form of increased understanding, knowledge and insight into white snapper farming and harvesting 1,005 white snapper weighing between 90-200 grams within 80 days of maintenance. The expected output is training and white snapper farming, students get enough knowledge and skills about white snapper farming technology to get a job and entrepreneurship with sufficient income, and get 20 credits of experience outside the campus. This activity can help pond farmers in increasing income and welfare.